Effect of Body Position and Support Surface on the Postural Control Challenge During the Pallof Press Exercise: A Smartphone Accelerometer-Based Study - Casto Juan-Recio; Amaya Prat-Luri; Heidy Rondón-Espinosa; David Barbado; Francisco J. Vera-Garcia (Medicina)
Background and objectives: Although different variations of the Pallof press exercise are commonly performed in sports and fitness settings to increase core stability, the intensity/difficulty of these variations is unknown and therefore it is difficult to control the training load and establish exercise progressions. This study aimed to compare and rank the postural control challenge imposed by five different isometric variations of the Pallof press exercise through a smartphone accelerometer placed on the participants’ pelvis and to explore sex differences in the lumbopelvic postural control during the exercise performance. Materials and Methods: Twelve physically active participants completed two testing sessions in which they performed two sets of five different isometric variations of the Pallof press exercise (changing the body position and/or the support surface: kneeling on a foam pad, feet together standing on the floor, tandem stance on the floor, feet together standing on a hemisphere ball, and tandem stance on a hemisphere ball). After confirming the acceleration data reliability (intraclass correlation coefficients ≥ 0.72 and typical errors ≤ 17%), a repeated measure ANOVA was carried out to classify the Pallof press variations according to the postural control challenge imposed on the participants and to analyze sex differences on postural control. Results: Significant effects were found for the within-subject factor exercise variations but not for the between-subject factor sex. Pairwise comparisons showed that the exercise variations performed on the hemisphere ball (feet together standing: 0.55 m/s2; tandem stance: 0.61 m/s2) imposed higher postural control demands than those performed on the other surfaces (kneeling on a foam pad: 0.17 m/s2; feet together standing on the floor: 0.22 m/s2; tandem stance on the floor: 0.31 m/s2). In addition, the tandem stance on the floor produced higher lumbopelvic accelerations than the Pallof press kneeling variation. Conclusions: The Pallof press performance in standing rather than kneeling (i.e., reducing the base of support and raising the center of gravity and the height of the lateral force applied by the elastic band) and on a hemisphere ball increased the exercise difficulty compared to more stable surfaces. This information could help to modulate the difficulty and establish progressions for this exercise in physically active young males and females.